Cathode active material for non-aqueous electrolyte secondary battery and method for manufacturing the same
Patent Information
- Application Number
- JP2024215368
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2040-09-30
Smart Images

Figure 2025026650000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a positive electrode active material for a non-aqueous electrolyte secondary battery and a method for producing the same. [Background technology]
[0002] High output characteristics are required for positive electrode active materials for non-aqueous electrolyte secondary batteries used in large power equipment such as electric vehicles. A positive electrode active material having a structure of secondary particles in which many primary particles are aggregated is considered effective for obtaining high output characteristics. For example, Patent Document 1 describes a positive electrode active material containing secondary particles composed of primary particles of two types of positive electrode active materials having different compositions, and is considered to be able to obtain high output in a wide range of states of charge (SOC). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2015-130272 A Summary of the Invention [Problem to be solved by the invention]
[0004] As a method for obtaining high output characteristics, it is considered to reduce the particle size of the positive electrode active material and increase the specific surface area. However, when the particle size of the positive electrode active material is reduced, the flowability of the positive electrode active material as a powder decreases, and the productivity tends to decrease. One aspect of the present disclosure aims to provide a positive electrode active material for a non-aqueous electrolyte secondary battery that improves the output characteristics during formation of the positive electrode and improves the flowability of the powder, and a method for producing the same. [Means for solving the problem]
[0005] The first aspect is the 50% particle size in the volume cumulative particle size distribution. 1 D 50a first lithium transition metal composite oxide having a particle size of 0.1 μm or more and less than 3.2 μm and a liquid medium; and granulating the composition to obtain a 50% particle size in a volume cumulative particle size distribution. 2 D 50 but 1 D 50 and obtaining a second lithium transition metal composite oxide having a volume cumulative particle size distribution that differs before and after ultrasonic treatment in a liquid medium, and a 90% particle size in the volume cumulative particle size distribution measured before ultrasonic treatment. 2 D 90 is the 90% particle size in the volume cumulative particle size distribution measured after ultrasonic treatment. 3 D 90 The ratio ( 3 D 90 / 2 D 90 ) is less than or equal to 0.53.
[0006] The second aspect includes a lithium transition metal composite oxide whose volume cumulative particle size distribution changes after ultrasonic treatment in a liquid medium, and the lithium transition metal composite oxide has a 90% particle size in the volume cumulative particle size distribution measured before the ultrasonic treatment. 2 D 90 is the 90% particle size in the volume cumulative particle size distribution measured after ultrasonic treatment. 3 D 90 The ratio ( 3 D 90 / 2 D 90 ) is 0.53 or less. Effect of the Invention
[0007] According to one aspect of the present disclosure, it is possible to provide a positive electrode active material for a non-aqueous electrolyte secondary battery, which has improved output characteristics during formation of a positive electrode and improved flowability as a powder, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] In this specification, the term "step" refers not only to an independent step, but also to a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved. In addition, the content of each component in the composition means the total amount of the multiple substances present in the composition when multiple substances corresponding to each component are present in the composition, unless otherwise specified. Hereinafter, the embodiments of the present invention will be described in detail. However, the embodiments shown below are examples of positive electrode active materials for non-aqueous electrolyte secondary batteries and methods for producing the same for embodying the technical idea of the present invention, and the present invention is not limited to the positive electrode active materials for non-aqueous electrolyte secondary batteries and methods for producing the same shown below.
[0009] Method for producing positive electrode active material for non-aqueous electrolyte secondary battery The method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery is to form a material having a particle size of 50% in a volume cumulative particle size distribution. 1 D 50 a preparation step of preparing a composition including a first lithium transition metal composite oxide having a particle size of 0.1 μm or more and less than 3.2 μm and a liquid medium; and granulating the prepared composition to obtain a 50% particle size in a volume cumulative particle size distribution. 2 D 50 but 1 D 50 and a granulation step of obtaining a second lithium transition metal composite oxide having a particle size larger than 90% in the volume cumulative particle size distribution measured before and after the ultrasonic treatment in a liquid medium. 2 D 90 is the 90% particle size in the volume cumulative particle size distribution measured after ultrasonic treatment. 3 D 90 The ratio ( 3 D 90 / 2 D 90 ) is less than or equal to 0.53.
[0010] Relatively small particle size (50% particle size in the volume cumulative particle size distribution) 1 D 50The composition is granulated to obtain a composition containing a liquid medium and primary particles (first lithium transition metal composite oxide) containing a lithium transition metal composite oxide having a particle size of 0.1 μm or more and less than 3.2 μm, and the composition is granulated to obtain a composition containing a liquid medium and a primary particle having a relatively large particle size (a particle size of 50% in the volume cumulative particle size distribution) in which the primary particles are aggregated. 2 D 50 The above 1 D 50 Secondary particles (second lithium transition metal composite oxide) having a particle size larger than that of the secondary particles are formed. The large particle size of the secondary particles improves the flowability of the powder, and the productivity of the positive electrode active material containing the secondary particles is improved. Here, productivity means, for example, suppression of clogging of a sieve. The secondary particles formed by granulation have a volume cumulative particle size distribution that differs before and after ultrasonic treatment in a liquid medium, and are 90% particle size in the volume cumulative particle size distribution measured before ultrasonic treatment. 2 D 90 is the 90% particle size in the volume cumulative particle size distribution measured after ultrasonic treatment. 3 D 90 The ratio ( 3 D 90 / 2 D 90 ) is 0.53 or less, it is believed that primary particles are regenerated when ultrasonically treated in a liquid medium. In general, an electrode active material layer is formed from a liquid electrode composition containing a positive electrode active material. When an electrode composition is prepared using a positive electrode active material containing granulated secondary particles, primary particles are regenerated in the electrode composition. Therefore, the positive electrode active material layer formed from the electrode composition contains the positive electrode active material which is a primary particle. The positive electrode active material which is a primary particle has a relatively large specific surface area due to its particle size, and it is believed that it can achieve high output characteristics in a battery.
[0011] In the preparation process, the 50% particle size in the volume cumulative particle size distribution is 1 D 50 A composition containing a first lithium transition metal composite oxide having a particle size of 0.1 μm or more and less than 3.2 μm and a liquid medium is prepared. 1 D 50From the viewpoint of output characteristics when a battery is constructed, the particle size is preferably 0.12 μm or more and 2.5 μm or less, and more preferably 0.13 μm or more and 2 μm or less. The 50% particle size is determined as the particle size corresponding to 50% of the volume cumulative from the small particle size side in the volume cumulative particle size distribution.
[0012] The first lithium transition metal composite oxide has a 90% particle size in a volume cumulative particle size distribution. 1 D 90 From the viewpoint of output characteristics when constituting a battery, for example, the particle diameter is 0.13 μm or more and 5 μm or less, and preferably 0.15 μm or more and 3 μm or less. The 90% particle diameter is determined as the particle diameter corresponding to 90% of the volume cumulative from the small particle diameter side in the volume cumulative particle size distribution.
[0013] 50% particle size of the first lithium transition metal composite oxide 1 D 50 and 90% particle size 1 D 90 can be controlled by appropriately selecting the particle size of the composite oxide used as the raw material and the heat treatment conditions when producing the first lithium transition metal composite oxide. 1 D 50 However, the lithium transition metal composite oxide having a particle size of 3.2 μm or more may be pulverized to obtain a desired particle size distribution. The pulverization may be, for example, wet pulverization in a liquid medium using a ball mill or the like, or dry pulverization using a jet mill or the like.
[0014] The first lithium transition metal composite oxide may be, for example, any one of a lithium transition metal composite oxide having a layered structure, a lithium transition metal composite oxide having an olivine structure, and a lithium transition metal composite oxide having a spinel structure.
[0015] As the lithium transition metal composite oxide having a layered structure, the lithium transition metal composite oxide containing cobalt may be lithium cobalt oxide. Lithium cobalt oxide contains a metal element M in addition to lithium and cobalt. 1 The metal element M may include at least one of the following: 1Examples of the metal oxide include nickel (Ni), manganese (Mn), aluminum (Al), magnesium (Mg), calcium (Ca), titanium (Ti), zirconium (Zr), niobium (Nb), thallium (Ta), chromium (Cr), molybdenum (Mo), iron (Fe), copper (Cu), silicon (Si), tin (Sn), bismuth (Bi), gallium (Ga), yttrium (Y), samarium (Sm), erbium (Er), cerium (Ce), neodymium (Nd), lanthanum (La), cadmium (Cd), and lutetium (Lu). At least one selected from the group consisting of these metal oxides may be used.
[0016] In the cobalt-containing lithium transition metal composite oxide having a layered structure, the ratio of the number of moles of cobalt to the total number of moles of metals other than lithium may be, for example, 1 or less.
[0017] A lithium transition metal composite oxide containing cobalt having a layered structure is 1 If lithium is included, the metal element M is the total number of moles of metals other than lithium. 1 The molar ratio may be, for example, 0.1 or less.
[0018] In the cobalt-containing lithium transition metal composite oxide having a layered structure, the ratio of the number of moles of lithium to the total number of moles of metals other than lithium may be, for example, 0.9 or more and 1.2 or less.
[0019] The cobalt-containing lithium transition metal composite oxide having a layered structure may have a composition represented by the following formula (1), for example. Li p Co x M 1 y O2(1) In formula (1), 0.9≦p≦1.2, 0 <x≦1、0≦y≦0.1、x+y≦1である。M 1is at least one selected from the group consisting of Ni, Mn, Al, Mg, Ca, Ti, Zr, Nb, Ta, Cr, Mo, Fe, Cu, Si, Sn, Bi, Ga, Y, Sm, Er, Ce, Nd, La, Cd, and Lu.
[0020] As the lithium transition metal composite oxide having a layered structure, the lithium transition metal composite oxide containing nickel contains at least lithium (Li) and nickel (Ni). The lithium transition metal composite oxide containing nickel may contain at least one selected from the group consisting of cobalt (Co), manganese (Mn) and aluminum (Al) in addition to lithium and nickel. The lithium transition metal composite oxide containing nickel may contain at least one selected from the group consisting of lithium, nickel, cobalt, manganese and aluminum in addition to the metal element M. 2 The metal element M 2 Examples of the metal include zirconium (Zr), titanium (Ti), magnesium (Mg), tantalum (Ta), niobium (Nb), and molybdenum (Mo), and may be at least one selected from the group consisting of these.
[0021] In the nickel-containing lithium transition metal composite oxide having a layered structure, the ratio of the number of moles of nickel to the total number of moles of metals other than lithium may be, for example, 0.3 or more and less than 1.
[0022] When the nickel-containing lithium transition metal composite oxide having a layered structure contains cobalt, the ratio of the number of moles of cobalt to the total number of moles of metals other than lithium may be, for example, 0.7 or less.
[0023] When the nickel-containing lithium transition metal composite oxide having a layered structure contains manganese, the ratio of the number of moles of manganese to the total number of moles of metals other than lithium may be, for example, 0.7 or less.
[0024] When the nickel-containing lithium transition metal composite oxide having a layered structure contains aluminum, the ratio of the number of moles of aluminum to the total number of moles of metals other than lithium may be, for example, 0.7 or less.
[0025] The layered structure of the lithium transition metal composite oxide containing nickel is 2 If lithium is included, the metal element M is the total number of moles of metals other than lithium. 2 The molar ratio may be, for example, 0.02 or less.
[0026] In the nickel-containing lithium transition metal composite oxide having a layered structure, the ratio of the number of moles of lithium to the total number of moles of metals other than lithium may be, for example, 1.0 or more and 1.5 or less.
[0027] The nickel-containing lithium transition metal composite oxide having a layered structure may have a composition represented by the following formula (2), for example. Li p Ni x Co y Mn z Al w M 2 u O2(2) In formula (2), 1.0≦p≦1.5, 0.3≦x<1, 0≦y≦0.7, 0≦z≦0.7, 0≦w≦0.7, 0≦u≦0.02, and x+y+z+w+u≦1. M 2 is at least one selected from the group consisting of Zr, Ti, Mg, Ta, Nb and Mo.
[0028] As the lithium transition metal composite oxide having an olivine structure, the iron-containing lithium transition metal composite oxide contains at least lithium (Li), iron (Fe) and phosphorus (P). The iron-containing lithium transition metal composite oxide contains the metal element M in addition to lithium, iron and phosphorus. 3 The metal element M 3Examples of the metal element include cobalt (Co), manganese (Mn), and nickel (Ni), and at least one selected from the group consisting of these may be used. The lithium transition metal composite oxide containing iron is a composite oxide containing lithium, iron, phosphorus, and a metal element M. 3 In addition to the metal element M 4 The metal element M 4 Examples of the metal include molybdenum (Mo), magnesium (Mg), zirconium (Zr), titanium (Ti), aluminum (Al), cerium (Ce), and chromium (Cr), and may be at least one selected from the group consisting of these.
[0029] In the iron-containing lithium transition metal composite oxide having an olivine structure, the ratio of the number of moles of iron to the total number of moles of metals other than lithium may be, for example, more than 0 and may be 1 or less.
[0030] The lithium transition metal composite oxide containing iron having an olivine structure is 3 If lithium is included, the metal element M is the total number of moles of metals other than lithium. 3 The ratio of the number of moles of may be, for example, less than 1.
[0031] The lithium transition metal composite oxide containing iron having an olivine structure is 4 If lithium is included, the metal element M is the total number of moles of metals other than lithium. 4 The molar ratio may be, for example, 0.3 or less.
[0032] In the iron-containing lithium transition metal composite oxide having an olivine structure, the ratio of the number of moles of lithium to the total number of moles of metals other than lithium may be, for example, 0.9 or more and 1.3 or less.
[0033] The iron-containing lithium transition metal composite oxide having an olivine structure may have a composition represented by the following formula (3), for example. Li p Fe x M 3 y M4 z PO4(3) In formula (3), 0.9≦p≦1.3, 0 <x≦1、0≦y<1、0≦z≦0.3、x+y+z≦1である。M 3 is at least one selected from the group consisting of Co, Mn and Ni. 4 is at least one selected from the group consisting of Mo, Mg, Zr, Ti, Al, Ce and Cr.
[0034] As the lithium transition metal composite oxide having a spinel structure, the manganese-containing lithium transition metal composite oxide contains at least lithium (Li) and manganese (Mn). The manganese-containing lithium transition metal composite oxide contains the metal element M in addition to lithium and manganese. 5 The metal element M 5 Examples of the metal oxide include aluminum (Al), magnesium (Mg), silicon (Si), titanium (Ti), chromium (Cr), iron (Fe), cobalt (Co), copper (Cu), zinc (Zn), and gallium (Ga), and may be at least one selected from the group consisting of these.
[0035] In the manganese-containing lithium transition metal composite oxide having a spinel structure, the ratio of the number of moles of Mn to the total number of moles of metals other than lithium may be, for example, more than 0 and may be 2 or less.
[0036] The lithium transition metal composite oxide containing manganese having a spinel structure is 5 If lithium is included, the metal element M is the total number of moles of metals other than lithium. 5 The molar ratio may be, for example, 0.2 or less.
[0037] In the type lithium transition metal composite oxide having a spinel structure and containing manganese, the ratio of the number of moles of lithium to the total number of moles of metals other than lithium may be, for example, 1 or more and 1.4 or less.
[0038] The lithium transition metal composite oxide having a spinel structure may have a composition represented by the following formula (4), for example. Li p Mn x M 5 y O4(4) In formula (4), 1≦p≦1.4, 0 <x≦2、0≦y≦0.2、x+y≦2である。M 5 is at least one selected from the group consisting of Al, Mg, Si, Ti, Cr, Fe, Co, Cu, Zn and Ga.
[0039] As the lithium transition metal composite oxide having a spinel structure, the lithium transition metal composite oxide containing nickel and manganese contains at least lithium (Li), nickel (Ni) and manganese (Mn). The lithium transition metal composite oxide containing nickel and manganese contains lithium, nickel and manganese as well as the metal element Mn. 6 The metal element M 6 Examples of the metal oxide include aluminum (Al), magnesium (Mg), silicon (Si), titanium (Ti), chromium (Cr), iron (Fe), cobalt (Co), copper (Cu), zinc (Zn), and gallium (Ga), and may be at least one selected from the group consisting of these.
[0040] In the lithium transition metal composite oxide containing nickel and manganese and having a spinel structure, the ratio of the number of moles of nickel to the total number of moles of metals other than lithium may be, for example, 0.3 or more and 0.6 or less.
[0041] In the lithium transition metal composite oxide containing nickel and manganese and having a spinel structure, the ratio of the number of moles of manganese to the total number of moles of metals other than lithium may be, for example, 1.2 or more and 1.7 or less.
[0042] A lithium transition metal composite oxide containing nickel and manganese having a spinel structure is 6If lithium is included, the metal element M is the total number of moles of metals other than lithium. 6 The molar ratio may be, for example, 0.2 or less.
[0043] In the lithium transition metal composite oxide containing nickel and manganese and having a spinel structure, the ratio of the number of moles of lithium to the total number of moles of metals other than lithium may be, for example, 1 or more and 1.4 or less.
[0044] The lithium transition metal composite oxide containing nickel and manganese and having a spinel structure may have a composition represented by the following formula (5), for example. Li p Ni x Mn y M 6 z O4(5) In formula (5), 1≦p≦1.4, 0.3≦x≦0.6, 1.2≦y≦1.7, 0≦z≦0.2, and x+y+z≦2. 6 is at least one selected from the group consisting of Al, Mg, Si, Ti, Cr, Fe, Co, Cu, Zn and Ga.
[0045] The liquid medium contained in the composition is preferably water from the viewpoint of the binding property between particles of the second lithium transition metal composite oxide, and may further contain a water-soluble organic solvent such as alcohol or acetone in addition to water. The composition may be configured as a slurry having fluidity. The solid content concentration of the first lithium transition metal composite oxide in the composition may be, for example, 5% by mass or more and 30% by mass or less, and preferably 10% by mass or more and 20% by mass or less.
[0046] The composition may contain other components in addition to the first lithium transition metal composite oxide and the liquid medium depending on the binding property between particles of the second lithium transition metal composite oxide. Examples of other components include a binder and a dispersant. When the composition contains other components, the content of the other components may be, for example, 10% by mass or less, preferably 5% by mass or less, more preferably 1% by mass or less. The lower limit of the content may be, for example, 0.01% by mass or more.
[0047] The composition can be prepared by mixing the first lithium transition metal composite oxide with a liquid medium. For example, the composition can be prepared by mixing using a mixer equipped with an agitating blade. The composition obtained by mixing may be subjected to a dispersion treatment. The dispersion treatment can be performed in a wet manner using, for example, a ball mill.
[0048] In the granulation step, the composition to be prepared is granulated to obtain a 50% particle size distribution of the particle size. 2 D 50 but 1 D 50 The second lithium transition metal composite oxide obtained has a volume cumulative particle size distribution that differs before and after ultrasonic treatment in a liquid medium, and has a 90% particle size in the volume cumulative particle size distribution measured before ultrasonic treatment. 2 D 90 is the 90% particle size in the volume cumulative particle size distribution measured after ultrasonic treatment. 3 D 90 The ratio ( 3 D 90 / 2 D 90 ) is less than or equal to 0.53.
[0049] In the granulation step, the composition to be prepared is dried to remove at least a part of the liquid medium, and the granulation step is performed to obtain a granulation composition having a particle size of 50% in the volume cumulative particle size distribution. 2 D 50 but 1 D 50 The second lithium transition metal composite oxide having a particle size larger than that of the first lithium transition metal composite oxide is obtained as a dried product. Methods for drying the composition include spray drying, fluidized bed drying, and the like. Spray drying is preferred because it is easy to adjust the particle size of the second lithium transition metal composite oxide.
[0050] 50% particle size of the second lithium transition metal composite oxide 2 D 50From the viewpoint of flowability as a powder, the particle size may be, for example, 2 μm or more, preferably 2.3 μm or more, and more preferably 2.5 μm or more. 2 D 50 may be, for example, 50 μm or less, preferably 30 μm or less, and more preferably 15 μm or less. The 50% particle size is determined as the particle size corresponding to 50% of the volume cumulative from the small particle size side in the volume cumulative particle size distribution.
[0051] The second lithium transition metal composite oxide has a particle size of 90% in a volume cumulative particle size distribution. 2 D 90 From the viewpoint of flowability as a powder, the particle size is sufficient to be larger than 3.6 μm, preferably 5 μm or more, and more preferably 6 μm or more. 2 D 50 may be, for example, 55 μm or less, preferably 35 μm or less, and more preferably 25 μm or less. The 90% particle size is determined as the particle size corresponding to 90% of the volume cumulative from the small particle size side in the volume cumulative particle size distribution.
[0052] The ratio of the 50% particle size of the second lithium transition metal composite oxide to the 50% particle size of the first lithium transition metal composite oxide ( 2 D 50 / 1 D 50 From the viewpoint of flowability as a powder, the ratio ( 2 D 50 / 1 D 50 ) may be, for example, 500 or less, and preferably 300 or less.
[0053] The ratio of the 90% particle size of the second lithium transition metal composite oxide to the 90% particle size of the first lithium transition metal composite oxide ( 2 D 90 / 1 D 90 From the viewpoint of flowability as a powder, the ratio ( 2 D 90 / 1D 90 ) may be, for example, 500 or less, and preferably 300 or less.
[0054] The second lithium transition metal composite oxide has a different volume cumulative particle size distribution before and after ultrasonic treatment in a liquid medium. The second lithium transition metal composite oxide is formed as a granule (secondary particles) of the first lithium transition metal composite oxide, which is a primary particle. Since the physical strength of the granule is low, at least a part of the granule disintegrates and regenerates the primary particles when an appropriate energy is applied. Therefore, by irradiating the second lithium transition metal composite oxide with ultrasonic waves in a liquid medium, at least a part of the primary particles constituting the granule are regenerated, and the particle size distribution changes. For example, when the particle size is 50% in the volume cumulative particle size distribution of the second lithium transition metal composite oxide constituting the positive electrode active material, 2 D 50 and 90% particle size 2 D 90 are the 50% particle diameters measured after the second lithium transition metal composite oxide is ultrasonically treated in a liquid medium, 3 D 50 and 90% particle size 3 D 90 Here, the ultrasonic treatment conditions in this specification are that 0.05 g of the second lithium transition metal composite oxide is dispersed in 200 ml of water containing 0.05 mass % of sodium hexametaphosphate, and ultrasonicated for 20 seconds at 20° C. using an ultrasonic irradiation device with a frequency of 40 kHz and an output of 110 W.
[0055] The second lithium transition metal composite oxide has a 50% particle size measured after ultrasonic treatment in a liquid medium. 3 D 50 However, from the viewpoint of output characteristics when a battery is constructed, the particle size is, for example, 0.1 μm or more and less than 3.2 μm, and preferably 0.11 μm or more and 2.5 μm or less. The 50% particle size is determined as the particle size corresponding to 50% of the volume cumulative from the small particle size side in the volume cumulative particle size distribution.
[0056] The second lithium transition metal composite oxide has a 90% particle size measured after ultrasonic treatment in a liquid medium. 3 D 90 From the viewpoint of output characteristics when the powder is used to configure a battery, the particle size is, for example, 0.1 μm to 5 μm, and preferably 0.15 μm to 3 μm. The 90% particle size is determined as the particle size corresponding to 90% of the volume cumulative from the small particle size side in the volume cumulative particle size distribution.
[0057] The second lithium transition metal composite oxide has the following characteristics in terms of output characteristics when used to construct a battery: 2 D 90 for 3 D 90 The ratio ( 3 D 90 / 2 D 90 ) may be, for example, greater than 0 and equal to or less than 0.53, preferably equal to or less than 0.5, and more preferably equal to or less than 0.3.
[0058] The second lithium transition metal composite oxide has the following characteristics in terms of output characteristics when used to construct a battery: 2 D 50 for 3 D 50 The ratio ( 3 D 50 / 2 D 50 ) may be, for example, greater than 0 and equal to or less than 0.53, preferably equal to or less than 0.5, and more preferably equal to or less than 0.3.
[0059] The first lithium transition metal composite oxide has a 50% particle size in a volume cumulative particle size distribution. 1 D 50 is the 50% particle size measured after ultrasonic treatment of the second lithium transition metal composite oxide in a liquid medium. 3 D 50 The ratio ( 3 D 50 / 1 D 50 ) is, for example, 0.8 or more and 1.5 or less, and preferably 0.95 or more and 1.1 or less, from the viewpoint of output characteristics when a battery is constructed.
[0060] The first lithium transition metal composite oxide has a 90% particle size in a volume cumulative particle size distribution. 1 D 90 is the 90% particle size measured after ultrasonic treatment in a liquid medium of the second lithium transition metal composite oxide. 3 D 90 The ratio ( 3 D 90 / 1 D 90 ) is, for example, 0.8 or more and 2 or less, and preferably 0.95 or more and 1.5 or less, from the viewpoint of output characteristics when a battery is constructed.
[0061] The second lithium transition metal composite oxide is formed, for example, by spray-drying the composition. The conditions, device, etc. for spray-drying may be appropriately selected. For example, the composition is dispersed in a drying chamber of a spraying device equipped with one or more nozzles for introducing the composition and one or more nozzles for an air flow, and at least a part of the liquid medium is removed from the composition to obtain the desired dried product. The conditions, such as the flow rate of each nozzle, the flow rate ratio between each nozzle, and the temperature of the drying chamber, may be selected from the following: 1 D 50 Greater than 2 D 50 and the particle size is 90% in the volume cumulative particle size distribution measured before ultrasonic treatment in a liquid medium. 2 D 90 is the 90% particle size in the volume cumulative particle size distribution measured after ultrasonic treatment. 3 D 90 The ratio ( 3 D 90 / 2 D 90 ) should be adjusted to be 0.53 or less.
[0062] Specific conditions for spray drying include, for example, the ratio of the amount of gas supplied to the amount of composition supplied of 500 to 4000, and preferably 800 to 2000. The drying temperature may be, for example, 100° C. to 170° C., and preferably 130° C. to 160° C.
[0063] It is preferable not to perform additional heat treatment on the second lithium transition metal composite oxide obtained by spray drying. Here, additional heat treatment means applying heat to the second lithium transition metal composite oxide at, for example, 250°C or higher, preferably 300°C or higher. When additional heat treatment is performed, the adhesive force between the primary particles is improved, and the collapse of the secondary particles may be suppressed.
[0064] Positive electrode active material for non-aqueous electrolyte secondary batteries The positive electrode active material for a non-aqueous electrolyte secondary battery contains a lithium transition metal composite oxide whose volume cumulative particle size distribution changes after ultrasonic treatment in a liquid medium. The lithium transition metal composite oxide has a 90% particle size in the volume cumulative particle size distribution measured before the ultrasonic treatment. 2 D 90 is the 90% particle size in the volume cumulative particle size distribution measured after ultrasonic treatment. 3 D 90 The ratio ( 3 D 90 / 2 D 90 ) is less than or equal to 0.53.
[0065] By forming the positive electrode active material containing a lithium transition metal composite oxide whose volume cumulative particle size distribution changes after ultrasonic treatment in a liquid medium, the positive electrode active material has excellent flowability as a powder. In addition, the volume cumulative particle size distribution changes after ultrasonic treatment, and the ratio ( 3 D 90 / 2 D 90 ) is 0.53 or less, high output characteristics can be achieved when a non-aqueous electrolyte secondary battery is constructed.
[0066] The lithium transition metal composite oxide constituting the positive electrode active material may be, for example, the second lithium transition metal composite oxide produced by the above-mentioned production method. Details of the second lithium transition metal composite oxide are as described above.
[0067] Non-aqueous electrolyte secondary battery electrode The electrode for a non-aqueous electrolyte secondary battery includes a current collector and a positive electrode active material layer disposed on the current collector and containing the positive electrode active material for a non-aqueous electrolyte secondary battery produced by the above-mentioned production method. A non-aqueous electrolyte secondary battery including such an electrode can achieve high initial efficiency and high durability.
[0068] Examples of the material of the current collector include aluminum, nickel, stainless steel, etc. The positive electrode active material layer can be formed by applying a positive electrode composition obtained by mixing the above-mentioned positive electrode active material, conductive material, binder, etc. with a solvent onto the current collector, and then performing drying treatment, pressure treatment, etc. Examples of the conductive material include natural graphite, artificial graphite, acetylene black, etc. Examples of the binder include polyvinylidene fluoride, polytetrafluoroethylene, polyamide acrylic resin, etc.
[0069] Nonaqueous electrolyte secondary battery The non-aqueous electrolyte secondary battery comprises the above-mentioned electrode for non-aqueous electrolyte secondary battery as a positive electrode. The non-aqueous electrolyte secondary battery comprises, in addition to the electrode for non-aqueous electrolyte secondary battery, a negative electrode for non-aqueous electrolyte secondary battery, a non-aqueous electrolyte, a separator, etc. In the non-aqueous electrolyte secondary battery, the negative electrode, non-aqueous electrolyte, separator, etc., for example, those for non-aqueous electrolyte secondary batteries described in JP 2002-075367 A, JP 2011-146390 A, JP 2006-12433 A (the entire disclosures of which are incorporated herein by reference) can be appropriately used. EXAMPLES
[0070] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0071] First, the methods for measuring physical properties in the following Examples and Comparative Examples will be described. 1 D 50 , 2 D 50 and 3 D 50 and, 1 D 90 ,2 D 90 and 3 D 90 The cumulative particle size distribution on a volume basis was measured using a laser diffraction particle size distribution measuring device (MASTER SIZER), and the 50% and 90% particle sizes corresponding to the cumulative 50% and 90% from the small diameter side were calculated. 1 D 50 and 1 D 90 The measurements were performed on the prepared lithium transition metal composite oxide after ultrasonic treatment (frequency: 40 kHz, output: 110 W, 20°C, 20 seconds, 0.05 mass % of sodium hexametaphosphate dispersant added to 200 mL of pure water). 3 D 50 and 3 D 90 Regarding 2 D 50 The lithium transition metal composite oxides for which the above properties were measured were subjected to ultrasonic treatment (frequency: 40 kHz, output: 110 W, 20° C., 20 seconds, 0.05 mass % of sodium hexametaphosphate dispersant was added to 200 mL of pure water) and then the measurements were performed.
[0072] Example 1 Precursor preparation An aqueous solution of cobalt sulfate was added dropwise to the stirred pure water at 60°C and 650 rpm. At the same time, an aqueous solution of 7.9 mol / L of sodium hydroxide was added dropwise to adjust the pH to 8.0. After the addition of the aqueous solution of cobalt sulfate was completed, the aqueous solution of sodium hydroxide alone was added dropwise until the pH was between 9.4 and 9.8, obtaining a precipitate containing cobalt. The obtained precipitate was filtered, washed with water, and then heat-treated at 330°C for 17 hours to obtain a composite oxide containing cobalt.
[0073] Preparation of lithium transition metal composite oxides Lithium carbonate was weighed out so that the molar ratio of lithium to cobalt in the cobalt-containing composite oxide was 1.01, and the cobalt-containing composite oxide and lithium carbonate were dry-mixed to obtain a lithium mixture. The obtained lithium mixture was heat-treated in air at 700°C for 5 hours, and then continuously heat-treated at 800°C for 5 hours to obtain a sintered body.
[0074] Distributed Processing The obtained sintered body was put into pure water to prepare a slurry with a slurry concentration of 20 mass %. The obtained slurry was dispersed for 150 minutes using a ball mill (φ0.65 mm, zirconium oxide pellets) to obtain a dispersion slurry. The physical properties of the first lithium transition metal composite oxide in the obtained dispersion slurry ( 1 D 50 , 1 D 90 ) are shown in Table 1.
[0075] spray drying The obtained dispersion slurry containing the lithium transition metal composite oxide was introduced into a spray nozzle at a flow rate of 16 mL / min and air at a flow rate of 30 L / min, and spray drying was carried out at a drying temperature of 250° C. to obtain a positive electrode active material of Example 1 containing a second lithium transition metal composite oxide. The physical properties ( 2 D 50 , 2 D 90 , 3 D 50 , 3 D 90 ) are shown in Table 1.
[0076] Comparative Example 1 A dispersion slurry containing a first lithium transition metal composite oxide was obtained in the same manner as in Example 1. The obtained dispersion slurry was filtered using a Buchner funnel (filter paper: ADVANTEC qualitative filter paper, 5C, 285 mm), and the obtained filtrate was left to stand and dried at a drying temperature of 150°C to obtain a positive electrode active material containing the lithium transition metal composite oxide of Comparative Example 1. The physical properties of the lithium transition metal composite oxide of Comparative Example 1 ( 2 D 50 , 2 D90 , 3 D 50 , 3 D 90 ) are shown in Table 1.
[0077] Comparative Example 2 A sintered body was obtained in the same manner as in Example 1, except that the heat treatment conditions for the lithium mixture were changed to heat treatment in an air atmosphere at 700°C for 5 hours, followed by a continuous heat treatment at 880°C for 5 hours. The obtained sintered body was dispersed for 15 minutes in a dry vibration mill (Chuo Kakoki B-2 type, UX-Φ25Fe core), and the obtained dispersion was then poured into pure water to prepare a dispersion slurry with a slurry concentration of 20 mass%. The physical properties of the lithium transition metal composite oxide in the obtained dispersion slurry ( 1 D 50 , 1 D 90 ) are shown in Table 1.
[0078] The dispersion slurry obtained above was dried in the same manner as in Comparative Example 1 to obtain a positive electrode active material containing a lithium transition metal composite oxide of Comparative Example 2. The physical properties of the lithium transition metal composite oxide of Comparative Example 2 ( 2 D 50 , 2 D 90 , 3 D 50 , 3 D 90 ) are shown in Table 1.
[0079] Comparative Example 3 After spray drying in the same manner as in Example 1, the mixture was further heat-treated at 400° C. in air to obtain a positive electrode active material containing a lithium transition metal composite oxide of Comparative Example 3. 2 D 50 , 2 D 90 , 3 D 50 , 3 D 90 ) are shown in Table 1.
[0080] Sieving speed 300 g of the lithium transition metal composite oxide obtained in Example 1 and Comparative Examples 1 to 3 was sieved for 60 seconds using a 30 cm diameter sieve with 70 μm openings (Gyro Sifter, 60 Hz), and the passing amount per unit area (kg / h m) was measured. 2 The results are shown in Table 1.
[0081] (Preparation of positive electrode) 11.6 g of the lithium transition metal composite oxide obtained in Example 1 and Comparative Examples 1 to 3 was mixed with 1.5 g (0.12 g as PVDF) of a solution in which polyvinylidene fluoride (hereinafter PVDF) was dissolved in N-methyl-2-pyrrolidone (hereinafter NMP), and then 1.2 g (0.24 g as AB) of acetylene black (hereinafter AB) solution was further added and mixed to obtain a positive electrode composition. The positive electrode composition was mixed with NMP so that the concentration of the positive electrode composition was 58 mass% to prepare an NMP slurry. The obtained NMP slurry was applied to an aluminum foil as a current collector and dried to obtain a dried product. The dried product was compression molded with a roll press machine and then cut to a predetermined size to produce a positive electrode.
[0082] (Preparation of negative electrode) A graphite material was used as the negative electrode active material. 97.5 parts by mass of the negative electrode active material, 1.5 parts by mass of carboxymethyl cellulose (CMC), and 1.0 parts by mass of styrene butadiene rubber (SBR) were dispersed in water and kneaded to prepare a negative electrode paste. This was applied to a current collector made of copper foil and dried, and after drying, it was compression molded with a roll press and then cut to a specified size to prepare a negative electrode.
[0083] [Preparation of non-aqueous electrolyte] Ethyl carbonate and methyl ethyl carbonate were mixed in a volume ratio of 3:7 to obtain a mixed solvent. The obtained mixed solvent was added with lithium hexafluorophosphate at a concentration of 1.0 mol. % to obtain a non-aqueous electrolyte solution.
[0084] [Assembly of non-aqueous electrolyte secondary batteries] Attach lead electrodes to the positive and negative electrode current collectors, respectively, and then vacuum dry at 120°C. Next, a separator made of porous polyethylene was placed between the positive electrode and the negative electrode, These were stored in a bag-shaped laminate pack. After storage, they were vacuum dried at 60°C and attached to each component. After vacuum drying, the nonaqueous electrolyte solution was injected into the laminate pack and sealed. A laminate-type nonaqueous electrolyte secondary battery was obtained as a battery for evaluation. The battery characteristics were evaluated as follows using the obtained battery for evaluation.
[0085] [Average voltage] After constant current and constant voltage charging at a full charge voltage of 4.45 V and a charge rate of 0.2 C, constant current discharging was performed at a discharge rate of 2 C with a discharge voltage of 2.0 V. The time average of the battery voltage during constant current discharging at a discharge rate of 2 C was taken as the average voltage. The results are shown in Table 1.
[0086] [Table 1]
[0087] As shown in Table 1, a positive electrode active material with excellent sieving speed could be obtained by forming granulated secondary particles in Example 1. In addition, in Example 1, the primary particles were regenerated when the granulated secondary particles were used to prepare an electrode, and the average voltage increased, so that a positive electrode active material with excellent output characteristics could be obtained.
Claims
1. The particle size is 50% in the cumulative volume particle size distribution. 1 D 50 preparing a composition including a first lithium transition metal composite oxide having a particle size of 0.1 μm or more and less than 3.2 μm, and a liquid medium; The composition is granulated to obtain a particle size of 50% in the volume cumulative particle size distribution. 2 D 50 The above 1 D 50 and obtaining a second lithium transition metal composite oxide having a molecular weight greater than or equal to the second lithium transition metal composite oxide has a volume cumulative particle size distribution that differs before and after ultrasonic treatment in a liquid medium; The particle size is 90% in the volume cumulative particle size distribution measured before ultrasonic treatment. 2 D 90 is the 90% particle size in the volume cumulative particle size distribution measured after ultrasonic treatment 3 D 90 The ratio ( 3 D 90 / 2 D 90 ) is 0.53 or less; The first lithium transition metal composite oxide has a composition represented by the following formula (1), (3) or (4): Li p Co x M 1 y O 2 (1) (In formula (1), 0.9≦p≦1.2, 0<x≦1, 0≦y≦0.1, and x+y≦1. M 1 is at least one selected from the group consisting of Ni, Mn, Al, Mg, Ca, Ti, Zr, Nb, Ta, Cr, Mo, Fe, Cu, Si, Sn, Bi, Ga, Y, Sm, Er, Ce, Nd, La, Cd and Lu. Li p Fe x M 3 y M 4 z 2O 4 (3) (In formula (3), 0.9≦p≦1.3, 0<x≦1, 0≦y<1, 0≦z≦0.3, and x+y+z≦1. M 3 is at least one selected from the group consisting of Co, Mn and Ni. 4 is at least one selected from the group consisting of Mo, Mg, Zr, Ti, Al, Ce and Cr. Li p Mn x M 5 y O 4 (4) (In formula (4), 1≦p≦1.4, 0<x≦2, 0≦y≦0.2, and x+y≦2. M 5 is at least one selected from the group consisting of Al, Mg, Si, Ti, Cr, Fe, Co, Cu, Zn and Ga.
2. The method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 , wherein the granulation is carried out by spray-drying the composition to remove at least a part of the liquid medium.
3. The second lithium transition metal composite oxide is 2 D 90 The method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein the particle size is greater than 3.6 μm.
4. The second lithium transition metal composite oxide has a 50% particle size in a volume cumulative particle size distribution measured after ultrasonic treatment. 3 D 50 The method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 , wherein the average particle diameter is less than 3.2 μm.
5. The above 1 D 50 is a 50% particle size in a volume cumulative particle size distribution measured after ultrasonic treatment of the second lithium transition metal composite oxide. 3 D 50 The ratio ( 3 D 50 / 1 D 50 5. The method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the ratio of the total mass of the positive electrode active material to the total mass of the non-aqueous electrolyte secondary battery is 0.8 or more and 2 or less.
6. A lithium transition metal composite oxide having a volume cumulative particle size distribution that changes after ultrasonic treatment in a liquid medium, The lithium transition metal composite oxide has a particle size of 90% in the volume cumulative particle size distribution measured before ultrasonic treatment. 2 D 90 is the 90% particle size in the volume cumulative particle size distribution measured after ultrasonic treatment 3 D 90 The ratio ( 3 D 90 / 2 D 90 ) is 0.53 or less; The lithium transition metal composite oxide has a composition represented by the following formula (1), (3) or (4), which is a positive electrode active material for a non-aqueous electrolyte secondary battery. Li p Co x M 1 y O 2 (1) (In formula (1), 0.9≦p≦1.2, 0<x≦1, 0≦y≦0.1, and x+y≦1. M 1 is at least one selected from the group consisting of Ni, Mn, Al, Mg, Ca, Ti, Zr, Nb, Ta, Cr, Mo, Fe, Cu, Si, Sn, Bi, Ga, Y, Sm, Er, Ce, Nd, La, Cd and Lu. Li p Fe x M 3 y M 4 z 2O 4 (3) (In formula (3), 0.9≦p≦1.3, 0<x≦1, 0≦y<1, 0≦z≦0.3, and x+y+z≦1. M 3 is at least one selected from the group consisting of Co, Mn and Ni. 4 is at least one selected from the group consisting of Mo, Mg, Zr, Ti, Al, Ce and Cr. Li p Mn x M 5 y O 4 (4) (In formula (4), 1≦p≦1.4, 0<x≦2, 0≦y≦0.2, and x+y≦2. M 5 is at least one selected from the group consisting of Al, Mg, Si, Ti, Cr, Fe, Co, Cu, Zn and Ga.
7. The lithium transition metal composite oxide is 2 D 90 The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 6, wherein the particle size is greater than 3.6 μm.
8. The lithium transition metal composite oxide has a particle size of 50% of the cumulative particle size distribution measured after ultrasonic treatment. 3 D 50 8. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 6, wherein the particle size is less than 3.2 μm.
Citation Information
Patent Citations
Electrode material for lithium ion secondary battery, method for manufacturing the same, lithium ion secondary battery electrode, and lithium ion secondary battery
JP2018056034A
Information processing device, information processing method and information processing program
JP2023026081A
Lithium titanium composite oxide comprising aluminum-coated primary particles and manufacturing method therefor
WO2019177328A1
Positive electrode for nonaqueous secondary battery, positive electrode active material for nonaqueous secondary battery, nonaqueous secondary battery and on-vehicle nonaqueous secondary battery
JP2015130272A